PERLINDUNGAN HUKUM BAGI APARATUR SIPIL NEGARA TERHADAP PELAYANAN PUBLIK PADA KANTOR WILAYAH ATR/BPN PROVINSI SUMATERA BARAT - Aridal Nova Daltim (UNES Journal of Swara Justisia, 2021)
Civil servants have an important role to play in carrying out development tasks and services to the community, this is stated in Law No. 5 of 2014 concerning ASN. In carrying out its duties, a Civil Servant (PNS) cannot be separated from the shortcomings and strengths that he does, one example of violations committed by the State Civil Apparatus of the Agam National Land Agency with alleged cases of corruption and misuse of certificates of shop houses (shophouses), kiosks in Lubuk Basung Old Market. The formulation of the problem in this research is, First, what is the legal protection for the State Civil Apparatus in providing services to the public at the ATR / BPN office of West Sumatra Province? Second, How is the effectiveness of the work of the State Civil Apparatus in public services at the West Sumatra Province ATR / BPN office? The specification of this research is descriptive analysis. The method used in this thesis research is to use a normative juridical approach which is supported by an empirical juridical approach, namely research in addition to looking at normative law also looks at the Legal Protection of State Civil Servants for public services in ATR / BPN West Sumatra Province. Based on the results of the research, it shows that (1) Legal protection for the State Civil Apparatus in providing services to the public at the ATR / BPN office of West Sumatra Province is in fact still not optimal because reforming the bureaucracy aimed at increasing the efficiency and effectiveness of the bureaucracy has not been carried out properly and obligations the government provides protection has not been realized and protection has not been issued. So that in case of negligence or mistakes made by ASN, the government only orders the Government Inspectorate to make efforts to resolve the problem. (2) The effectiveness of the work of the State Civil Apparatus in public services at the ATR / BPN office of West Sumatra Province is still not effective at this time. This is because there are several problems that have occurred and have not been resolved properly. For example, this happened when an ASN was sentenced because of an error in the HGB Management Rights service and the ASN did not get legal assistance, the government only made efforts to resolve the Building Use Rights case.